Physicochemical characterization of chronic venous ulcer exudates by FTIR Spectroscopy - Cerúsico, Nicolás Abel (2017)
Chronic venous legulcer (CLVU) arises as a complication of chronic venous insufficiency. Thishigh recurrence pathology has an overall prevalence ranging up to 2% in generalpopulation, causing an important reduction in life quality and large financial costsfor patients and health care system. To get a better diagnostic and treatment,it?s crucial to identificate the parametersinvolved in this pathology, being the exudate(wound fluid) composition a biochemical representation of the clinical state ofa wound. Fourier Transform Infrared (FTIR) spectroscopy associated to otherclinical parameters would help to get a clinical represent-image for each case.The aim of this work is topropose FTIR spectroscopy as a novel and versatile technique to get a physico-chemicalcharacterization of exudate samples to get abetter diagnostic in a less-invasive and simply way.